The Articulation of Healthy Water Closet Program in Kabuaran Village of Bondowoso: Analysing Society’s Behavioural Change in Defecation - Nisa, Wardani Khoirun; Handayani, Baiq Lily (Laboratorium Sosiologi FISIP Universitas Jember, 2019)
The people in Kabuaran village used to defecate haphazardly. Since a sanitation program for healthy closet was promulgated, the people have been used to using water closet. To date, the village has been renowned as Open Defecation Free (ODF) Village, which is national award endowed to an area where the poeple no longer defecate haphazardly. The present study applied qualitative approach. The paradigm founded the study was criticism paradigm, coupled with the theory of Hegemony and Gramsci domination, adopted from Marx. The research findings evinced that the public behavioural change represented government’s control, actualized by local government. The synergy was a structure operationalized for positive behavioural change to stop haphazard defecating. Numerous innovations and initiatives were carried out by the village government, be it providing public toilet, clean water program, and water closet provision. It was at this juncture that domination mechanism was at work. In this regard, the village government accidentally involved traditional intellects, religious figures, to take part in accruing public awareness, which was done in hegemonic manner through regular Al-Qur’an recital. Keywords: Behavioural change, domination, hegemony, traditional intellects. Referensi: Djik, Kees van. 2011. Soap is The Onset of Civilization. Dalam van Djik, Kees., & Jean G. Taylor. Cleanliness and Culture: Indonesia Histories. Leiden: KITLV Press Foucault, Michael. 2002. Wacana Kuasa/Pengetahuan. Diterjemahkan oleh: Yudi Santosa. Jogjakarta: Bentang Budaya Patria, Nezar, dan Andi Arief. 2015. Antonio Gramsci: Negara dan Hegemoni. Yogyakarta: Pustaka Pelajar. Simajuntak, B., dan Pasaribu I. L. 1986. Sosiologi Pembangunan. Bandung: Penerbit TARSITO. Sphere, Proyek. 2004. Keamanan dan Standar Minimum dalam Respon Bencana. Jakarta: PT Grasindo. Sugiyono, Muhadi. 1999. Kritik Antonio Gramsci terhadap Pembangunan Dunia Ketiga. Yogyakarta: Pustaka Pelajar. Susan, Novri. 2008. Pengantar Sosiologi Konflik dan Isu-isu Konflik Kontemporer. Jakarta: Kencana Prenada. Tilaar, H. A. R. 2003. Kekuasaan dan Pendidikan: Suatu Tinjauan dari Perspektif Studi Kultural). Magelang: IndonesiaTera. Zuriah, Nurul. 2009. Metode Penelitian Sosial dan Pendidikan. Jakarta: Bumi Aksara Rio, Sutanto Boby. 2015. Perilaku Masyarakat dalam Pemanfaatan Sarana Mandi Cuci Kakus (MCK): Studi Deskriptif Warga Desa Candijati Kecamatan Arjasa Kabupaten Jember. Universitas Jember: Jurusan Kesejahteraan Sosial. Munthe, Hadriana Nurhaeni. 2007. Modernisasi dan Perubahan Sosial Masyarakat dalam Pembangunan Pertanian: Suatu Tinjauan Sosiologis. Medan: Universitas Sumatera Utara. Jurnal Harmoni Sosial Volume II No. 1.